The role of addition of calcium alginate microcapsules on permanent deformation of AC–WC natural asphalt Buton stone in Indonesia - Desvita, Melly Dwi; Djakfar, Ludfi; Wisnumurti; Prasetia, Muhammad Syarif; Febriansyah, Muhammad Chaidar (Eastern-European Journal of Enterprise Technologies, 2023)
This paper discusses natural asphalt deposits of Buton stone (asbuton) in Indonesia are very abundant, but the characteristics of asbuton are not yet suitable for road applications. So that the use of asbuton as a binder needs to be added with additives that can react independently to overcome the permanent deformation such as the addition of calcium alginate microcapsules to the asphalt mixture. The purpose of this study was to determine the effect of adding calcium alginate microcapsules to the permanent deformation of AC-WC with asbuton. The current problem is that road pavements are not able to heal themselves when cracks start to occur, so additional materials are needed that can stimulate self-healing to occur so that the cracks that have started to occur can be closed again even though it takes time so that the self-healing process can occur. The microcapsules are made with the main ingredients of water, sunflower oil, sodium alginate (C6H7O6Na) and calcium chloride solvent (CaCl2), which are encapsulated and embedded in the asphalt mixture as a material that can restore the structural function by a healing method self healing. The research method uses true experimentally. Specimen variations in the study were the addition of calcium alginate microcapsules of 0 %, 1 %, 1.5 %, 2 %. Wheel Tracking Testing was carried out with the AASHTO Standard: T 32-11 and CAL Testing with the Tex-245-F 2014 standard. The results showed that with the addition of calcium alginate microcapsules, there was no significant contribution; better than microcapsules, the mixture decreases in the number of passes so that the mixture is easy to change shape rutting. However, adding calcium alginate microcapsules can reduce the value of weight loss, causing the adhesion of the asphalt mixture to increase